2008
DOI: 10.1038/oby.2008.146
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and C-reactive Protein Levels Among White, Black, and Hispanic US Adults

Abstract: Objective-Studies suggest that obesity's adverse impact on cardiovascular mortality may be reduced in African Americans relative to white Americans. We examined whether obesity's association with novel cardiovascular risk factors such as C-reactive protein (CRP) also varies by race and ethnicity.Methods and Procedures-We analyzed data from 10,492 white, African-American, and Hispanic-American participants of the 1999-2004 National Health and Nutrition Examination Survey, who were aged 20 years and older, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…Increased serum CRP levels have been reported in subjects with obesity, metabolic syndrome, and type 2 diabetes (T2D), indicating that these individuals present a state of subclinical, low-grade inflammation that promotes the development of atherosclerosis mediated by a process of endothelial dysfunction, increasing the risk of ischemic heart disease (Wee et al, 2008;Hu et al, 2009). Serum CRP levels vary widely among individuals and, in the absence of disease, are influenced by socio-demographic factors, lifestyle, and significantly, gender, and obesity (Flores-Alfaro et al, 2008;Wee et al, 2008;Tsai and Tsai, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased serum CRP levels have been reported in subjects with obesity, metabolic syndrome, and type 2 diabetes (T2D), indicating that these individuals present a state of subclinical, low-grade inflammation that promotes the development of atherosclerosis mediated by a process of endothelial dysfunction, increasing the risk of ischemic heart disease (Wee et al, 2008;Hu et al, 2009). Serum CRP levels vary widely among individuals and, in the absence of disease, are influenced by socio-demographic factors, lifestyle, and significantly, gender, and obesity (Flores-Alfaro et al, 2008;Wee et al, 2008;Tsai and Tsai, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Serum CRP levels vary widely among individuals and, in the absence of disease, are influenced by socio-demographic factors, lifestyle, and significantly, gender, and obesity (Flores-Alfaro et al, 2008;Wee et al, 2008;Tsai and Tsai, 2010). It has been shown that variation in CRP influences the concentration of protein (Carlson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence suggests that many of these obesity associated co-morbidities have a long term low grade inflammatory basis (3). Among inflammatory biomarkers, the role of classic inflammatory mediators including tumor necrosis factor α (TNF-α) and C-reactive protein (CRP) have been extensively investigated in obesity (4,5). However, recent studies have revealed the possible role of Th17-T cell sub-lineage in obesity associated metabolic and autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…33 However, another study reports no difference in the association between BMI and CRP among European Americans versus African Americans. 34 A better understanding of racial differences in relationships among BMI and inflammation may advance understanding of racial differences in the predictive value of BMI for various conditions, including outcomes unique to pregnancy.…”
mentioning
confidence: 99%